Mechanical and Electrical Equipment for Buildings - Grondzik, Walter T.; Kwok, Alison G. (Hoboken, New Jersey : Wiley, 2020)
The most widely-used text on the design of environmental control systems in buildings for students and practicing professionals, Mechanical and Electrical Equipment for Buildings has for generations prepared students of architecture, architectural engineering, and construction for what they need to know about building systems and controlling a building's environment. With over 2,200 drawings and photographs, the Thirteenth Edition covers basic theory, preliminary building design guidelines, and detailed design procedure for buildings of all sizes, and also provides information on the latest technologies, emerging design trends, and updated codes
Includes index.
Keywords: Buildings -- Electric equipment; Buildings -- Mechanical equipment; Buildings -- Environmental engineering